Characterization and Application of a New β-Galactosidase Gal42 From Marine Bacterium Bacillus sp. BY02 - Zhou, Zihan; He, Ningning; Han, Qi; Liu, Songshen; Xue, Ruikun; Hao, Jianhua; Li, Shangyong (Frontiers in Microbiology, 2021)
β-Galactosidase plays an important role in medicine and dairy industry. In this study, a new glycoside hydrolase family 42 (GH42) β-galactosidase-encoding gene, gal42, was cloned from a newly isolated marine bacterium Bacillus sp. BY02 and expressed in Escherichia coli. Structural characterization indicated that the encoding β-Galactosidase, Gal42, is a homotrimer in solution and homology modeling indicated that it retains the zinc binding sites of the Cys cluster. The reaction activity of Gal42 was significantly increased by Zn2+ and other divalent metal ions (Mn2+, Mg2+ and Co2+), while, its activity was inhibited by EDTA. Meanwhile, the thermo-stability of the Gal42 was also significantly enhanced by zinc ions supplement, which suggested that the "Cys-Zn" motif played important roles in both of structural stability and catalytic function. Furthermore, Gal42 showed effective lactose hydrolysis activity, which makes the enzyme hydrolyze the lactose in milk effectively. These properties make Gal42 a potential candidate in food technology.